Uma abordagem para construção e reutilização de componentes de software com implementação em Delphi - Moraes, João Luis Cardoso de (2004)
This project searches a boarding for construction and reuse of software components with implementation in Delphi. More and more computational resources are used in the solution of problems, aiming to automatize them, to reduce costs and increase the efficiency, performance, and security. To take care of this demand of more trustworthy softwares systems, more efficient and with lesser costs, new methods have been searched, being distinguished, currently, the Component-Based Development (CBD). The research studies different methods, available techniques and tools in literature as: CBD, Design Patterns, Software Components, Model Language (MDL), and ObjectPascal Language (Delphi), as control for the boarding. The mechanism utilized are: MVCASE tool, Draco-PUC Transformation System (TS), Software Engineer, and Delphi (RAD). This integrated mechanisms orient the Software Engineer on the Construct and on the Components Reuse for aplication development, and MVCASE tool automatize the tasks for components construct and reuse. The boarding is divided in two stages: Construct Components and Reuse Components. In a first stage, the software engineer initial from the problem domain knowledge and produces a models components of the domain, implemented in a language orientedcomponents, in the case the Delphi. As soon as they are instaled, the components are keep in the repository for reuse. In a subsequent stage the software engineer will find the components about the problem domain, that are imported from MVCASE tool repository, where they are show in tool browser. After the components are identified the applications are developed that reuse the framework components constructed. The components may be implemented in language components oriented like, C++, Java, and ObejctPascal (Delphi). In this project we are using the ObjectPascal language for the components implementation.